Characterization of prodromal symptoms in a large population of patients with hereditary angio‐oedema. (1st April 2014) - Magerl, M.; Doumoulakis, G.; Kalkounou, I.; Weller, K.; Church, M. K.; Kreuz, W.; Maurer, M.
Summary: Background: Hereditary angio‐oedema (HAE) due to C1‐inhibitor (C1‐INH) deficiency is a rare autosomal dominant disease. It predisposes affected patients to attacks of disfiguring, painful angio‐oedema, which, in cases of involvement of the upper airways, can be life‐threatening. Frequently, prodromal symptoms occur hours to days before an attack, but their predictive value is uncertain. Aim: To characterize the spectrum of prodromal symptoms in patients with HAE in Germany. Methods: A questionnaire asking about the frequency, type and time of occurrence of prodromal symptoms, and the interval until the onset of an attack of HAE was sent to 808 German patients with HAE. Answers from 365 participating patients were analysed. Results: The survey showed that 79% of patients with HAE had experienced ≥ 1 prodromal symptom before an attack of angio‐oedema. The most commonly reported prodromal symptoms (67% of which occurred within 6 h before an attack) were fatigue, malaise and short temper. Significantly more women than men reported having prodromes (83% vs. 73%, P < 0.05). Over 90% of the patients with prodromes reported that they were able to predict the onset of an attack with a certainty of ≥ 50%. In addition, there was a significant correlation between the occurrence of skin rashes and delay in the diagnosis of HAE. Conclusions: The results of this survey may aid the management of C1‐HAE by recognizing that prodromal symptoms are of value in predicting the onset of an attack of angio‐oedema and in diagnosing the condition.